Variations of Catalase and Glutathione Activities in Molting Cycle of Mud Crab (Scylla serrata) - Salaenoi, Jintana; Srimeetian, Pattarawadee; Mingmuang, Mingkwan (Agriculture and Natural Resources, 2014)
The activities of the antioxidative enzyme, catalase (CAT), and the non-enzyme, glutathione (GSH) in 12 stages over the molting of mud crab (Scylla serrata) collected from Chanthaburi Province were determined. The stages were defined as: A1 (6-hour postmolt), A2.1 (12-hour postmolt), A2.2 (24-hour postmolt), B1 (2-day postmolt), B 2.1 (3-day postmolt), B2.2 ( 5-day postmolt), B2.3 (7-day postmolt), B2.4 (10 day postmolt), C (intermolt), D1 (2-week premolt), D2 (1- week premolt) and D3 (2-day premolt). The results revealed that CAT which controlled and eliminated excessive H2O2, increased in premolt (D1–D3) then dropped in the early postmolt stages (A1–A2.2) and increased again in the late postmolt stages (B1–B2.4). GSH, a reducing substance, which is also involved in the detoxification of H2O2 showed the same pattern in most tissues except in the hepatopancreas where it increased from the early postmolt stage (A1) and continued to increase through the postmolt stages. The variation in activity of CAT and GSH corresponded well with the metabolic activity through the molt cycle.